Perancangan Media Informasi Pengenalan Kebudayaan Dan Pariwisata Nias Selatan Berbasis Web - Gulo, Pontinus; Harianja, Andy Paul (LPPM UNIKA Santo Thomas Medan, 2018)
This study discusses the design of information media for the introduction of south nias culture which is a web-based application that uses the PHP and MySQL programming languages as its database. This system provides convenience to introduce culture and tourism in southern Nias in full, both in travel routes, lodging, tourist attractions, restaurants, souvenirs and visitors can provide comments and questions directly to the Admin. For tourism services this system is an convenience to run work programs that have been designed to promote culture and tourism in the southern Nias region more broadly.